2009 International Conference on CyberWorlds 2009
DOI: 10.1109/cw.2009.19
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Personal Space of Virtual Agents for Behavior Simulation

Abstract: Abstract-In this paper we propose a mathematical model for the concept of Personal Space (PS) and apply it to simulate the non-verbal communication between agents in virtual worlds. The distance between two persons reflects the type of their relationship. Human-like autonomous virtual agents should be equipped with such capability to simulate natural interactions. We define three types of relationships; (1) stranger relationship, (2) business relationship, and (3) friendly relationship. First we model the spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…As an essential aspect in social interactions, PS is a recurring subject of investigations. Being a non-verbal communication channel [4], human proxemic behavior, defined as the use of space in interpersonal interactions [15], reflects the nature of a relationship between an individual and its interactants. Thus, PS is considered as a personal safety zone humans try to maintain around themselves.…”
Section: Interpersonal Distancementioning
confidence: 99%
See 1 more Smart Citation
“…As an essential aspect in social interactions, PS is a recurring subject of investigations. Being a non-verbal communication channel [4], human proxemic behavior, defined as the use of space in interpersonal interactions [15], reflects the nature of a relationship between an individual and its interactants. Thus, PS is considered as a personal safety zone humans try to maintain around themselves.…”
Section: Interpersonal Distancementioning
confidence: 99%
“…Research indicated that the exact size and shape of an individual's PS depends on numerous factors [16]. Various personal and social characteristics, such as gender, age, culture, or affective expressions [4,20,40] impact the PS preferences as well as environmental factors, such as lighting and in-or outdoor location [1,12]. Often found are elliptically-shaped PS zones, with roughly twice as much space in the individual's front compared to its back and side areas [4].…”
Section: Interpersonal Distancementioning
confidence: 99%
“…Durupinar et al combined OCEAN personality model, pleasure‐arousal‐dominance model, and Ortony, Clore, and Collins model in crowd simulation. The modeling of the personal space also improves the social presence of virtual agents …”
Section: Related Workmentioning
confidence: 99%
“…Amaoka et al in [13] propose a mathematical model of personal space in order to apply it to agents in virtual worlds and simulate realistic behavior. They use two 2dimensional Gaussian functions which represent the personal space around an individual.…”
Section: B Roboticsmentioning
confidence: 99%